Carlyle, Emerson and the transatlantic uses of authority: literature, print, performance - Sommer, Tim (Interventions in Nineteenth-Century American Literature and Culture I19CALC, 2022)
Analyses Thomas Carlyle and Ralph Waldo Emerson against the background of Anglo-American print culture and oral performanceDevelops a new analytical framework for the study of nineteenth-century transatlantic writing that combines literary studies, book history and cultural sociologyReframes canonical works through unfamiliar texts and contextsDraws on a rich body of archival sources and historical periodical publicationsOffers an in-depth account of nineteenth-century Anglo-American print culture and the transatlantic lecture systemExamining the transatlantic writings and professional careers of Thomas Carlyle and Ralph Waldo Emerson, this book explores the impact of literary, cultural, political and legal manifestations of authority on nineteenth-century British and American writing, publishing and lecturing. Drawing on primary texts in conjunction with a rich body of archival sources, this study retraces Romantic debates about race and nationhood, analyses the relationship between cultural nationalism and literary historiography and sheds light on Carlyle’s and Emerson’s professional identities as publishing authors and lecturing celebrities on both sides of the Atlantic